Kinetics of kojic acid fermentation by Aspergillus flavus using different types and concentrations of carbon and nitrogen sources - Rosfarizan, M.; Ariff, A.B. (Nature Publishing Group, 2000)
Kinetics of kojic acid fermentation by Aspergillus flavus Link 44-1 using various sources of carbon [glucose, xylose, sucrose, starch, maltose, lactose or fructose] and nitrogen [NH4Cl, (NH4)2S2O8, (NH4)2NO3, yeast extract or peptone] were analyzed using models based on logistic and Luedeking-Piret equations. The highest kojic acid production (39.90 g l-1) in submerged batch fermentation was obtained when 100 g l-1 glucose was used as a carbon source. Organic nitrogen sources such as peptone and yeast extract were favorable for kojic acid production as compared to inorganic nitrogen sources. Yeast extract at 5 g l-1 was optimal. The optimal carbon to nitrogen (C/N) ratio for kojic acid fermentation was 93.3. In a resuspended cell system, the rate of glucose conversion to kojic acid by cell-bound enzymes increased with increasing glucose concentration up to 70 g l-1, suggesting that the reaction followed the Michaelis-Menten enzyme kinetic model. The value of K(m) and V(max) for the reaction was 18.47 g l-1 glucose and 0.154 g l-1 h-1, respectively.